FOSSIL WOODS FROM THE UPPER MIOCENE OF THE ERKOVETSKII BROWN COAL FIELD (AMUR RIVER REGION) - Blokhina N.I.; Snezhkova S.A. (My University, 2003)
Two new species, Laricioxylon priamnrensis and Populoxylon priaimtrensis, are described from the upper Miocene of the Erkovetskii brown coal field (Amur River Region) on the basis of wood anatomy. The former combines characters of the extant larches Larix olgensis, L. occidentalis, and L. leptolepis, while the latter is greatly reminiscent of the extant Populits maximowiczii and P. balsamifera. Populus-like fossil wood is recorded from the Russian Far East for the first time.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен